(untitled) (International journal of medical sciences, 2026)
This scientific article aims to comprehensively analyze the clinical significance of surgical resection of the 11th and 12th ribs for waist narrowing purposes, examining both aesthetic outcomes and functional consequences on respiratory mechanics, spinal stability, and visceral protection. A systematic literature review was conducted using PubMed, Scopus, and Web of Science databases between 2000 and 2024. Studies evaluating lower rib resection for aesthetic purposes, surgical techniques, complications, and functional outcomes were included. Data extraction focused on patient demographics, surgical indications, techniques, complications, and long-term follow-up results. Analysis of 23 eligible studies encompassing 847 patients who underwent floating rib resection revealed that waist circumference reduction averaged 4-8 cm postoperatively. Patient satisfaction rates ranged from 78% to 92%. However, significant complications were documented in 12-18% of cases, including pneumothorax (8%), chronic pain (6%), and rare but serious complications such as diaphragmatic dysfunction and liver/kidney injuries. Respiratory function tests demonstrated a mean reduction of 12-15% in forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) at 3 months postoperatively, with partial recovery at 12 months. While 11th-12th rib resection can achieve significant aesthetic improvements in waist contouring, the procedure carries substantial functional risks that require careful patient selection, thorough preoperative counseling, and meticulous surgical technique. The decision to perform this procedure should involve multidisciplinary evaluation including plastic surgeons, thoracic surgeons, and pulmonologists.